A Comparative Framework for Assessing Sustainability Initiatives at the Regional Scale. (October 2017) - Orenstein, Daniel E.; Shach-Pinsley, Dalit
Highlights: Regional sustainability initiatives can be characterized by their focus, structure, and scale. Particular qualities of an initiative can influence its potential for success. A combined top-down/bottom-up, socio-ecological, and focused yet holistic thematic approach is recommended. Summary: "Sustainability" has been a prominent goal in environmental and spatial planning over the past three decades. A diverse array of initiatives have been proposed and implemented with the aim of facilitating human economic and social development, while mitigating or even reversing associated environmental damage. These initiatives vary in their definitions of sustainability, their targets for planning and management, their bureaucratic structures, and other characteristics. As such, a universally applicable "how-to" manual for realizing the goals of regional sustainable development remains elusive. The objective of this paper is to provide scholars and practitioners with a simple analytical framework for assessing objectives, strengths, and weaknesses of sustainability initiatives at the regional scale. Drawing upon a review of theoretical and applied research on regional sustainable development, we categorize initiatives into typologies, including (1) Natural resource and ecology-based; (2) Urbanism; (3) Issue-based; and, (4) Governance, participation and science-based. We analyze each according to their focus, scope, fields of action and activities, and successes and challenges. Through this analysis, we define axes that highlight the prominent differences in characteristics between diverse approaches to sustainability. These are: (1) "top-down—bottom-up", based on who initiates and maintains the sustainability initiative; (2) "ecological—socioeconomic", defining the relative emphasis on ecological and/or social systems; (3) "holistic—subject-specific", defining the initiatives' breadth of the planning and management focus; and (4) "regional-local", defining the spatial scale of the initiative. These axes are useful for highlighting considerations that may have been neglected within an initiative, possibly preventing successful outcomes. We suggest that successful sustainability initiatives are introspective and work progressively toward balance between the extremes of these axes. This conclusion is buttressed by the evolutionary development of three global-scale sustainability efforts initiated by UNESCO's Man and The Biosphere program, the International Long-Term Ecological Research Network, and the Urbanist movement.